Экология широкого щелкуна—Selatosomus latus Fabry (Coleoptera, Elateridae) в Европейской части СССР - Кабанов, В.А. (Вестник зоологии, 1973)
Selatosomus latus F a b r y is one of the most dangerous pest of cultural plants. It is especially numerous in the Forest-Steppe and Steppe zones of the Ukraine, Central Chernozem belt, North Caucasus and Volga river area. As a result of a detailed study of individual phases of development (egg, larva, pupa, imago), it was established that generation of S. latus in the premountain zone of the North Caucasus is accomplished for three years; in the Steppe and Forest-Steppe zones — for three-four years; in the north of the areal —for five years. In the process of development the larva passes through 10-14 ages.